The medium of the media - Kunelius, Risto (Javnost (Ljubljana), 2012)
In academic and popular discourse, the power of media in current globalised and "postdemocratic" societies is often discussed with the notion of "mediatisation". It suggests, for example, that media institutions are increasingly influential because they dictate the way issues are framed for public discussion. Consequently, other institutional actors (in politics, science, religion) have had to internalise a "media logic" in order to sustaintheir power and legitimate their actions. Recent studies of mediatisation largely ignore Jürgen Habermas' early use of the term "mediatization" in order to analyse the relationship between system imperatives and lifeworlds. While at first this use may seem distant to recentconcerns, a return to Habermas can enhance the theorising of mediatisation and media power in two ways. First, by underscoring the importance of a system-theoretic vocabulary it helps to unpack the notion of "media logic" and narrow down the specific power resource of the media (i.e. what is the "medium" of the media). Second, by articulating a fundamental criticism of system-theoretic vocabulary it opens a normative perspective for an evaluation of the media's democratic function (i.e. the ŽqualityŽ of mediatisation). This essay highlights, elaborates and illustrates each of these potential contributions by looking at journalism research in general anddrawing on a recent empirical study on the mediatisation of political decisionmaking in Finland.
Keywords: mass media; množični mediji; novinarstvo; journalism; javno obveščanje; družbena moč